ПСИХОЛОГІЧНІ І ЛІНГВІСТИЧНІ ОСНОВИ МЕТОДИКИ НАВЧАННЯ ГРАМОТИ ШЕСТИРІЧНИХ ПЕРШОКЛАСНИКІВ (Педагогіка вищої та середньої школи, 2022)
This article deals with the questtion about the development of speech and mental activity б year old children at lessons of studing grammar material in the ABC period and also peculierities of psycological and linguistical raund of methodics of studing grammar offirst form pupils.